Tetanus Toxin Fragment C: Structure, Drug Discovery Research and Production - Caroline Bayart; Angélique Mularoni; Nada Hemmani; Soumeya Kerachni; Joachim Jose; Patrice Gouet; Joseph Paladino; Marc Le Borgne (MDPI AG, 2022)
Tetanus toxoid (TTd) plays an important role in the pharmaceutical world, especially in vaccines. The toxoid is obtained after formaldehyde treatment of the tetanus toxin. In parallel, current emphasis in the drug discovery field is put on producing well-defined and safer drugs, explaining the interest in finding new alternative proteins. The tetanus toxin fragment C (TTFC) has been extensively studied both as a neuroprotective agent for central nervous system disorders owing to its neuronal properties and as a carrier protein in vaccines. Indeed, it is derived from a part of the tetanus toxin and, as such, retains its immunogenic properties without being toxic. Moreover, this fragment has been well characterized, and its entire structure is known. Here, we propose a systematic review of TTFC by providing information about its structural features, its properties and its methods of production. We also describe the large uses of TTFC in the field of drug discovery. TTFC can therefore be considered as an attractive alternative to TTd and remarkably offers a wide range of uses, including as a carrier, delivery vector, conjugate, booster, inducer, and neuroprotector.